The performance profile of Dioscorea rotundata cultivar Dorban genotypes in Ghana using GGE biplot analysis - Otoo, E.; Asiedu, Robert (2009)
Twenty-two genotypes of D. rotundata cultivar Dorban consisting of 19 botanically developed seeds and 3 vegetative checks were evaluated in 15 environments from 2000 to 2004 using CRD to assess the effect of genotype and genotype x environment interaction on the tuber yield of 22 white yam (D. rotundata L. cv. Dorban) genotypes via GGE (genotype plus genotype x environment) biplot ethodology. The GGE biplot procedure was used to determine the yield potential and stability of the genotypes. Significant differences (p<0.001) were observed in all cultivars with respect to genotype, environment and genotype by environment interactions. Biplot analysis identified three mega-environments corresponding to the three agroecologies - Fumesua (Forest) was the most representative and discriminating environment followed by Bodwease (Coastal Savannah) and Wenchi (Forest-Savannah Transition). Genotypes Gdo02, Gdo03, Gdo20 and Gdo01 including the three checks were identified as superior. GenotypeGdo016 was the worst genotype.